Chapter A study of economic inequality in the light of fiscal sources: the case of Catalonia (14th-18th centuries) - Morelló, Jordi (Datini Studies in Economic History, 2020)
This essay aims to present the first results of an ongoing research project devoted to study the evolution of the economic inequality in Catalonia based on different documentary sources and parameters. Here we focus on the strengths and limits of the rich fiscal sources preserved between the 14th and 18th century allowing us an analysis of inequality. This study is limited to the period before 1716 because we do not consider totally reliable connecting data from taxes before this moment, essentially focused on immovable wealth, with those from the Cadastre, which was levied on a wide range of incomes.